PENGARUH HASIL BELAJAR PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DENGAN MENERAPKAN MODEL TSTS BERBANTUAN ULAR TANGGA DI SDN PATI WETAN 03 - Rindiani Rindiani; Wawan Shokib Rondli; Deka Setiawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The learning process carried out in class V at SDN Pati Wetan 03 is still using lecture method and focused on the teacher. The use of this method is less effective in learning because students become less active. Therefore, the application of learning models and media has a strong influence on student activity and the achievement of learning goals. From this background, the researchers conducted a study of whether there was an influence of the TSTS model with the help of a snake media staircase on the learning outcome of V SD Pati Wetan 03. This research is a quantitative one group pretest-posttest design method. Learning results are measured using test-related instruments. The data analysis techniques used are normality tests and t-tests. T-test indicates the result of sig. 0,200>0,05 then this research data is normal. Whereas, on the test t-test shows the results of pretest-posttest with sign value. (2-tailed) 0,000<0,05 it can be concluded that there is an influence of learning results PPKn after applying the model TSTS assisted with snake stairs in students of grade V SD Pati Wetan 03.